2021
DOI: 10.1111/jam.15076
|View full text |Cite
|
Sign up to set email alerts
|

Breast milk flora plays an important role in infantile eczema: cohort study in Northeast China

Abstract: Aims: Infantile eczema, usually coupled with a range of hypersensitive phenotypes, has come into notice with its rising prevalence and unclear pathogenesis. Recent studies show close ties between eczema and an infant's intestinal flora. To gain a further understanding of the interactions between microbiota and eczema, we studied the breast milk flora as a new factor and present the links among breast milk flora, infant intestinal flora and infantile eczema through a cohort study in Northeast China. Methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…There is mounting evidence that the gut microbiota is crucial to the development of the immune system and the prevention of eczema in the periods of neonatal, infant, child, and adult [ 14 , 15 , 31 , 32 , 33 33 , 35 ]. Of these, several cross‐sessional studies [ 15 , 31 , 32 , 35 ] have obtained fecal samples of infants below 6 months of age, while others [ 14 , 33 ] performed longitudinal sampling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is mounting evidence that the gut microbiota is crucial to the development of the immune system and the prevention of eczema in the periods of neonatal, infant, child, and adult [ 14 , 15 , 31 , 32 , 33 33 , 35 ]. Of these, several cross‐sessional studies [ 15 , 31 , 32 , 35 ] have obtained fecal samples of infants below 6 months of age, while others [ 14 , 33 ] performed longitudinal sampling.…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence that the gut microbiota is crucial to the development of the immune system and the prevention of eczema in the periods of neonatal, infant, child, and adult [ 14 , 15 , 31 , 32 , 33 33 , 35 ]. Of these, several cross‐sessional studies [ 15 , 31 , 32 , 35 ] have obtained fecal samples of infants below 6 months of age, while others [ 14 , 33 ] performed longitudinal sampling. A longitudinal study of fecal microbiota of children from 5 weeks through 6–11 years has indicated that alterations in microbial diversity and composition precede the onset of allergic manifestations [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…mucinophila ) is said to contribute to a healthy mucus-associated microbial composition and could also be used to prevent obesity and type 2 diabetes [ 63 , 80 , 81 ]. It was found to be an indicator of healthy breast milk in humans and presumed to confer beneficial functions as a probiotic [ 82 ]. Therefore, its abundance in the studied body sites may be important for the health of cows.…”
Section: Discussionmentioning
confidence: 99%
“…230 Similar to other constituents of breast milk, the breast milk microbiota establishes a close association with the health of infants through the transmission of bacteria from mother to infant and its metabolic functions. 231 An randomized controlled trial (RCT) demonstrated that maternal uptake of a combination of three probiotics, LGG, L. acidophilus La-5, and B. lactis Bb-12, could reduce the cumulative incidence of AD; however, it did not affect atopic sensitization. 232 Perez et al have shown that maternal peripheral blood mononuclear cells and breast milk contain small amounts of viable bacteria and a wide range of bacterial DNA signatures.…”
Section: Targeting Intestinal Microorganisms and Gastrointestinal Bar...mentioning
confidence: 99%
“…230 Similar to other constituents of breast milk, the breast milk microbiota establishes a close association with the health of infants through the transmission of bacteria from mother to infant and its metabolic functions. 231…”
Section: Natural Products For the Treatment Of Admentioning
confidence: 99%